1998
DOI: 10.1038/sj.bmt.1701423
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic graft-versus-host disease after bone marrow transplantation: a retrospective single centre analysis

Abstract: Summary:Among 551 consecutive recipients of allogeneic bone marrow transplants, 451 survived more than 3 months and were evaluated for chronic graft-versus-host disease (GVHD). Most of the donors were HLA-identical siblings or parents (n = 334). Patients with HLA-mismatched donors (n = 30) and matched unrelated donors (MUD) (n = 87) were also included in the study. In the analysis of all patients, the 5-year cumulative incidence of chronic GVHD was 45%. We analysed 34 risk factors. High recipient age was the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
134
6
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 33 publications
15
134
6
5
Order By: Relevance
“…22,24 Regarding risk factors for ocular GVHD, several studies have suggested that prior acute skin GVHD was an independent predictor for ocular GVHD, 10,12 and we also observed that skin involvement during the acute and chronic stages was correlated with the onset of ocular GVHD. During the acute and chronic stages, GVHD in the gastrointestinal tract and liver was also correlated with the occurrence of ocular GVHD, as was GVHD in the oral mucosa and lungs during the chronic stage.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…22,24 Regarding risk factors for ocular GVHD, several studies have suggested that prior acute skin GVHD was an independent predictor for ocular GVHD, 10,12 and we also observed that skin involvement during the acute and chronic stages was correlated with the onset of ocular GVHD. During the acute and chronic stages, GVHD in the gastrointestinal tract and liver was also correlated with the occurrence of ocular GVHD, as was GVHD in the oral mucosa and lungs during the chronic stage.…”
Section: Discussionsupporting
confidence: 63%
“…A history of acute GVHD is known to be a strong risk factor for chronic GVHD development, [21][22][23][24] and other risk Values are n (%) unless otherwise specified.…”
Section: Discussionmentioning
confidence: 99%
“…21 Besides the T cells, antibodies against the H-Y antigen made by donor B cells probably also contribute to GVHD. 21,22 There are some reports that male recipients whose female donors had previous pregnancies or blood transfusions are at increased risk of developing GVHD, [23][24][25] apparently because of B-cell sensitization to the H-Y antigen. In this study, the previous donor pregnancies and transfusions was not checked.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Several studies have reported a history of acute GVHD to be a strong risk factor that is consistently associated with chronic GVHD development. [4][5][6][7][8] Other identified risk factors include the following: female donor and male recipient, 4,6 use of PBSC grafts, 6,9-13 older patient, 4,[6][7][8] older donor, 6,7 transplantation from a mismatched or unrelated donor, 5,6,14 diagnosis of CML 4,7,8 and absence of anti-thymocyte globulin (ATG) use. 15 The number of unrelated cord blood (U-CB) transplantations performed has rapidly increased during the past decade.…”
Section: Introductionmentioning
confidence: 99%